Assessing press releases as a data source for spatial research - Burcu Ozgun; Tom Brökel (REGION, 2022)
Describing the distribution and development of socio-economic activities in space is frequently limited due to data availability, as official statistical data sources are often restricted to specific topics and geographical scales. Consequently, new and alternative data sources are needed as complements. This paper presents, discusses, and empirically explores an example of such an alternative data source that promises to give detailed and novel insights into regions' socio-economic structures: press releases. While press releases have seen some use in the literature, they have hardly seen any applications in regional research. Consequently, it is still largely unknown to what extent their information content gives systematic insights into regional socio-economic patterns. The paper closes this gap by assessing the degree to which the content of press releases corresponds to the socio-economic characteristics of regions, by means of an empirical analysis of German NUTS-3 regions. The results confirm that press release content varies systematically between regions, and regional differences in socioeconomic characteristics, events, and activities seem to be well-presented by press releases. This suggests that press releases offer substantial potential and might be a useful complementary data source in regional studies.
Keywords: 330